Studi Kasus Perilaku Organisasi Di MAN Kota Sawahlunto: Inovasi Kepala Sekolah Dalam Menyiapkan Siswa Untuk Perguruan Tinggi Negeri - Arnol Arnol; Suswati Hendriani (Journal on Education, 2024)
This research aims to describe a case study of organisational behaviour in MAN Kota Sawahlunto with a focus on the principal's innovation in preparing students to continue their education to public universities. The type of research used is explorative with a qualitative approach. Descriptive analytic method is used to describe and answer the problem of existing phenomena, both in single variables and correlation or comparison of various variables. Data were collected through observation, interview, and documentation study. Data analysis used the Miles and Huberman model technique consisting of data reduction, data presentation, and verification and conclusion drawing. Based on the results of the study, there are several innovations implemented by the head of MAN Sawahlunto, which include building a conducive academic environment, improving the quality of teaching, career guidance, and counselling. These innovations proved to be effective in helping students achieve their goal of continuing their education to public universities. In addition, collaboration with public universities and regular monitoring of student progress are also integral parts of the holistic approach